Selección de cultivares avanzados de soya (Glycine max (L) Merril) por rendimiento y tolerancia a plagas, en la zona de La Esmeralda, Cantón Montalvo, Provincia de Los Ríos - Napa Cusme, Fabricio Floresmilo (2011)
The present job of investigation was carried during the dry weather on the 2011, at the Herrera family farm located in La Esmeralda parishioner to 12.30 km; from Montalvo city, Los Rios Province to 113 m.s.n.m. with the coordinate’s 01° 41´ 55’’ south latitude, 79° 16´ 29’’ west longitude. The specific objectives showed were: a) Evaluating 65 farming advanced of soybean from local and of other latitude in La Esmeralda zone, Montalvo city, Los Rios province, b) To select farming with good potential of rent and tolerant to the principal plagues that affect the farming with the end of decrease the application of pesticides and contribute with the reduction of the environment pollution. The experiment had a total area of 561.6 m², and it was grown in 5 rectangle blocks without the design experimental due to the quantity from the experiment, each block accounted 13 treatments and each treatment accounted with 4 rows of 4 m of long, with a separation between them of 0.45 m. In each row was grown 45 plants to regulate the poblation in each treatment to 250000 plants/ha.......